Genome-scale brain metabolic networks as scaffolds for the systems biology of neurodegenerative diseases: Mapping metabolic alterations - Özcan, Emrah; Cakir, Tunahan (Springer New York LLC barbara.b.bertram@gsk.com, 2018)
Systems-based investigation of diseases requires integrated analysis of cellular networks and high-throughput data of gene products. The use of genome-scale metabolic networks for such integration has led to the elucidation of cellular mechanisms for several cell types from microorganisms to plants. It has become easier and cheaper to generate high-throughput data over years in the form of transcriptome, proteome and metabolome. This has tremendously improved the quality and quantity of information extracted from such data enabling the documentation of active pathways and reactions in cell metabolism. A number of omics-based datasets for several neurodegenerative diseases are now available in public repositories. This increases the potential of using genome-scale brain metabolic networks as a scaffold for this type of data to map metabolic alterations for the purpose of elucidating disease mechanisms and for the diagnosis and treatment of such disorders. This chapter first reviews omics data collected for neurodegenerative diseases to map their effect on metabolism. Later, the potential for genome-scale metabolic modeling of such data is reviewed and discussed in light of recently reconstructed brain metabolic networks at genome-scale. © 2018 Elsevier B.V., All rights reserved.
Keywords: Alzheimer; Constraint-based modeling of metabolism; Genome-scale metabolic networks; Metabolic pathway enrichment; Metabolome; Neurodegenerative diseases; Parkinson; Reporter pathway analysis; Transcriptome